Gender and asthma-chronic obstructive pulmonary disease overlap syndrome. (8th August 2016) - Wheaton, Anne G.; Pleasants, Roy A.; Croft, Janet B.; Ohar, Jill A.; Heidari, Khosrow; Mannino, David M.; Liu, Yong; Strange, Charlie
Abstract: Objective : To assess relationships between obstructive lung diseases, respiratory symptoms, and comorbidities by gender. Methods : Data from 12 594 adult respondents to the 2012 South Carolina Behavioral Risk Factor Surveillance System telephone survey were used. Five categories of chronic obstructive airway disease (OAD) were defined: former asthma only, current asthma only, chronic obstructive pulmonary disease (COPD) only, asthma-COPD overlap syndrome (ACOS), and none. Associations of these categories with respiratory symptoms (frequent productive cough, shortness of breath, and impaired physical activities due to breathing problems), overall health, and comorbidities were assessed using multivariable logistic regression for men and women. Results : Overall, 16.2% of men and 18.7% of women reported a physician diagnosis of COPD and/or asthma. Former asthma only was higher among men than women (4.9% vs. 3.2%, t -test p = 0.008). Current asthma only was more prevalent among women than men (7.2% vs. 4.7%, p < 0.001), as was ACOS (4.0% vs. 2.2%, p < 0.001). Having COPD only did not differ between women (4.3%) and men (4.4%). Adults with ACOS were most likely to report the 3 respiratory symptoms. COPD only and ACOS were associated with higher likelihoods of poor health and most comorbidities for men and women. Current asthma only was also associated with these outcomes among women, but not among men. Conclusions : In this large population-based sample, women were more likely than men to report ACOS and current asthma, but not COPD alone. Gender differences were evident between the OAD groups in sociodemographic characteristics, respiratory symptoms, and comorbidities, as well as overall health.